The actor [videorecording (Blu-Ray)] - Cooney, Stephen; Johnson, Duke; Holland, André; Chan, Gemma, 1982- (Neon, 2025)
In this existential romance, New York actor Paul Cole finds himself stranded in a mysterious small town with no memory of who he is or how he got here. With no sense of identity or purpose, he starts from scratch and begins courting a local costume designer Edna. As bits and pieces of his past slowly emerge, he attempts to find his way home.